Monetary Policy and the Housing Market in Indonesia: Evidence from Selected Regions - Ariyanto Adhi Nugroho; M. Yusuf Indra Purnama; Laela Rizki Fauzia (Jurnal Keuangan dan Perbankan, 2018)
The housing market in Indonesia tends to have different characteristics in several regions. The government has implemented macroprudential policies regarding mortgage loans for housing and apartments through the Loan to Value (LTV) policy in dealing with credit risk in the housing market. The aimed of this study analyze the effect of LTV policy and regional economic indicator on the house prices in Indonesia, compare the impact of LTV policy and indicator on the types of houses and regions. We used secondary data from eight regions which derived from residential property survey and statistics Indonesia at a monthly frequency. In processing estimated data using Generalized Least Square (GLS) Fixed Effect Model (FEM) to ascertain the effect of LTV policy in each region. The result showed most attributes had a significant effect on housing prices. However, LTV had no significant effect on every type of housing (small, medium, and large). The LTV policy is spatial in accordance with housing market condition in each region.JEL Classification: E52, O18, R31DOI: https://doi.org/10.26905/jkdp.v22i4.2515